Climate change, carbon dependency and narratives of transition and stasis in four English rural communities. (December 2015) - Phillips, Martin; Dickie, Jennifer
Highlights: We explore carbon-dependency and people's awareness of it within 4 English villages. We examine people awareness of climate change with these villages. High levels of concern about energy and climate change but lower levels of action. Differences between attitude and action justified though narratives to the self. Identify 5 narratives of stasis and 3 narratives transition. Abstract: This paper explores the carbon dependency of life in four villages in England, the degree to which residents in these villages are aware of and concerned about this dependency and its relationship to climate change, and the extent to which they undertake actions that might mitigate or adapt to this dependency. The paper identifies high degrees of carbon dependency and awareness and concern about climate change and carbon dependency, although relatively low levels of mitigative or adaptive actions. The paper explores how this disjuncture between awareness and actions persists, arguing that attention needs to be paid to how people narrate stories to themselves and others that account for inaction. Five narratives of non-transition or stasis are identified, along with three, less widely adopted, narratives of transition. The significance of rurality and emotions within these narratives is highlighted.